2004
DOI: 10.1111/j.1469-8749.2004.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gastrostomy tube feeding on the quality of life of carers of children with cerebral palsy

Abstract: The aim of this prospective cohort study was to evaluate the impact of gastrostomy tube feeding on the quality of life of carers of children with cerebral palsy (CP). Short-Form 36 version II was used to measure quality of life in carers of 57 Caucasian children with CP (28 females, 29 males; median age 4y 4mo, range 5mo to 17y 3mo) six and 12 months after insertion of a gastrostomy tube. Responses were calibrated against a normative dataset (Oxford Healthy Life Survey III). Six months after gastrostomy feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
125
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 16 publications
14
125
1
3
Order By: Relevance
“…Some caregivers spend many hours a day trying to feed their disabled child and quality of life in parents of children with CP may be significantly impaired. 11 Feeding should not be stressful for caregiver or child. Ideally, the child and family will find feeding to be pleasurable.…”
Section: Efficiency: Is Feeding Efficient For the Child And For The Fmentioning
confidence: 99%
“…Some caregivers spend many hours a day trying to feed their disabled child and quality of life in parents of children with CP may be significantly impaired. 11 Feeding should not be stressful for caregiver or child. Ideally, the child and family will find feeding to be pleasurable.…”
Section: Efficiency: Is Feeding Efficient For the Child And For The Fmentioning
confidence: 99%
“…14,19 -21 Few case series of children with neurological impairment who have had a fundoplication have addressed child and caregiver quality of life following either a fundoplication or placement of a feeding tube. [22][23][24] In their study of 16 patients who had a fundoplication and gastrostomy tube placed, Tawfik et al found improvements in children's happiness, ease of giving medicines, and time to devote to other children. Sullivan et al found improvement in caregiver quality of life following placement of a gastrostomy tube in a child; however, they did not specifically identify those children who had been treated with a fundoplication.…”
mentioning
confidence: 99%
“…They generally worry less about their child's nutrition with the knowledge that they are getting sufficient via the tube. 12 Despite the benefits, the suggestion of a gastrostomy feeding tube (GFT) can generate opposition for some families. 13,14 For others, however, an alternative to feeding by mouth may come as a welcome relief.…”
Section: Introductionmentioning
confidence: 99%